2016
DOI: 10.1073/pnas.1602493113
|View full text |Cite
|
Sign up to set email alerts
|

Silk-based blood stabilization for diagnostics

Abstract: Advanced personalized medical diagnostics depend on the availability of high-quality biological samples. These are typically biofluids, such as blood, saliva, or urine; and their collection and storage is critical to obtain reliable results. Without proper temperature regulation, protein biomarkers in particular can degrade rapidly in blood samples, an effect that ultimately compromises the quality and reliability of laboratory tests. Here, we present the use of silk fibroin as a solid matrix to encapsulate bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
69
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 75 publications
(70 citation statements)
references
References 38 publications
(43 reference statements)
1
69
0
Order By: Relevance
“…In the past two decades, silk has undergone a technological revolution with a large body of research focused on engineering new material formats using the natural protein (extracted from the gland, or from silk fibers) as well as genetically engineered ones (especially, recombinant spider silk proteins). Silk materials have been fabricated into various material formats for biomedical applications with successful demonstrations in tissue engineering, drug stabilization and controlled delivery, and implantable medical devices . Furthermore, silk has also been widely used in flexible electronics, optical and photonic devices owing to the great flexibility and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In the past two decades, silk has undergone a technological revolution with a large body of research focused on engineering new material formats using the natural protein (extracted from the gland, or from silk fibers) as well as genetically engineered ones (especially, recombinant spider silk proteins). Silk materials have been fabricated into various material formats for biomedical applications with successful demonstrations in tissue engineering, drug stabilization and controlled delivery, and implantable medical devices . Furthermore, silk has also been widely used in flexible electronics, optical and photonic devices owing to the great flexibility and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to synthetic polymers based on chemical reactions, silkworm silk is a protein‐based material produced by silkworms at ambient conditions in an all‐aqueous reaction environment. Silk is thus produced in an environment‐friendly process, and due to biocompatibility and mechanical features shows potential for developing healthcare products, biomedical devices, and biosensors . The extraordinary mechanical properties of silk originate from the unique highly repetitive sequence in fibroin, along molecular self‐assembly and organization at nanoscale .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, silk was functionalized with ECM components that are expressed in the physiological bone marrow structure [7]. Importantly, it was previously shown that silk preserves the activity of the encapsulated molecules [13,15,16]. …”
Section: Discussionmentioning
confidence: 99%
“…Finally, a third system, made by PDMS, was developed with a wide array of von Willebrand Factor-coated micropillars supposed to act as anchors on Mks, allowing them to extend proplatelets under a hydrodynamic shear [11]. Compared to these systems for platelet production, a critical feature of our flow chamber is the use of natural silk protein biomaterial to leverage its versatility such as programmable mechanical properties, and surface binding of growth factors and ECM components, while retaining their bioavailability [13,16]. In our previous BM model we used silk tubes and sponges to recreate the vascular niche where Mks release platelets [16].…”
Section: Discussionmentioning
confidence: 99%